2019
DOI: 10.1093/aobpla/plz027
|View full text |Cite
|
Sign up to set email alerts
|

Investment in reward by ant-dispersed plants consistently selects for better partners along a geographic gradient

Abstract: Seed dispersal by ants (myrmecochory) is an asymmetric, presumably mutualistic interaction, where a few ant species benefit many plants. Myrmecochorous plants express specialized adaptations, most notably a large elaiosome, which promote interactions with efficient seed dispersers while decreasing interactions with poor dispersers, resulting in de facto partner choice. However, because variation in plants’ investment in reward and ant response to them may vary spatially and temporally, it is unclear whether su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 66 publications
0
9
1
Order By: Relevance
“…Contrary to our prediction, elaiosome mass, elaiosome width, and elaiosome-seed mass ratio were not significantly different among species. These results are not consistent with the results of several studies showing that ants prefer larger elaiosome biomass and/or elaiosome-seed mass ratios (Leal et al, 2014;Levine et al, 2019;Mark & Olesen, 1995), although they do support the finding that ants do not exert significant selection on elaiosome size in Helleborous foetidus . Considering that the most attractive species in our study, T. catesbaei, had smaller average elaiosome mass and smaller elaiosome-seed mass ratios than all of its congeners, these aspects of elaiosome morphology do not appear to be the most important factors contributing to the attractiveness of Trillium seeds to ants.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to our prediction, elaiosome mass, elaiosome width, and elaiosome-seed mass ratio were not significantly different among species. These results are not consistent with the results of several studies showing that ants prefer larger elaiosome biomass and/or elaiosome-seed mass ratios (Leal et al, 2014;Levine et al, 2019;Mark & Olesen, 1995), although they do support the finding that ants do not exert significant selection on elaiosome size in Helleborous foetidus . Considering that the most attractive species in our study, T. catesbaei, had smaller average elaiosome mass and smaller elaiosome-seed mass ratios than all of its congeners, these aspects of elaiosome morphology do not appear to be the most important factors contributing to the attractiveness of Trillium seeds to ants.…”
Section: Discussioncontrasting
confidence: 99%
“…Diaspore size, elaiosome biomass, and the elaiosome-seed mass ratio are all known to influence the attractiveness of diaspores to ants (Leal, Lima Neto, Oliveira, Andersen, & Leal, 2014;Mark & Olesen, 1995). Interspecific variation in elaiosome size and elaiosome-seed mass ratios is substantial, and these traits are often correlated (Edwards, Dunlop, & Rodgerson, 2006;Leal et al, 2014;Levine, Ben-Zevi, Seifan, & Giladi, 2019;Reifenrath, Becker, & Poethke, 2012), meaning any interpretation of the effects of one trait should be considered in light of the other. In many systems, effective ant dispersers prefer the seeds of species that produce heavier elaiosomes (Levine et al, 2019;Ness, Bronstein, Andersen, & Holland, 2004;Takahashi & Itino, 2015), although Manzaneda, Rey, and Alcántara (2009) found that ants exerted significant selection on seed size, but not on elaiosome size when both traits were considered simultaneously.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We further predict that the reduction in dispersal may originate from two, nonmutually exclusive, processes: First, plant‐mediated reduction in seed dispersal effectiveness may be related to lower elaiosome attractiveness at range margins. In general, the probability of a seed to be dispersed by a high‐quality disperser increases with elaiosome size or elaiosome/seed mass ratio (Edwards, Dunlop, & Rodgerson, 2006; Levine, Ben‐Zvi, Seifan, & Giladi, 2019; Mark & Olesen, 1996) and with the inclusion of higher concentrations of specific fatty acids (most prominently oleic acid) in the elaiosome content (Boulay, Coll‐Toledano, & Cerdá, 2006; Mayer, Ӧlzant, & Fischer, 2005). We hypothesized that plants in range margin populations, which inhabit small patches of suitable habitat, will produce smaller and less attractive elaiosomes, thus securing more localized dispersal than populations closer to the range core.…”
Section: Introductionmentioning
confidence: 99%
“…However, infrequently, seeds that are carried by granivorous ants may escape predation and be effectively dispersed, either along foraging trails or at refuse piles [ 6 , 18 , 19 ]. Harvester ants, which are among the more dominant members of the granivore guild, tend to exhibit little or no affinity to the presence or size of an elaiosome on a seed [ 20 , 21 ], thus dispersing myrmecochorous seeds only occasionally. Scavenging ants, on the other hand, ignore the seeds of most plant species, but exhibit high affinity for myrmecochorous seeds, which they transport over long-distances, bring to their nest, and leave intact after removing the elaiosome [ 13 ].…”
Section: Introductionmentioning
confidence: 99%